Impact of patient-centred home telehealth programme on outcomes in heart failure. (August 2019) - Srivastava, Anshul; Do, Jacquelyn-My; Sales, Virna L; Ly, Samantha; Joseph, Jacob
Background: Telehealth is a promising intervention to reduce readmissions and healthcare-associated costs in patients with heart failure. Methods: We performed a retrospective analysis of the impact of telehealth on 197 heart failure patients who had successfully completed one year of home telehealth monitoring following a heart failure admission as part of a clinically mandated programme at a Veterans Affairs Medical Center. Outcomes were compared both within the group (one year before and one year after home telehealth monitoring), and to a contemporary control cohort of 870 heart failure patients who were admitted but not enrolled in home telehealth. The following outcomes were analysed: admissions for any cause, heart failure admissions, total hospital days per patient, average length of stay per admission, urgent care and emergency room visits, and primary care visits. Results: Both the home telehealth and control cohorts consisted of older male patients. Total hospital days per patient was significantly reduced by home telehealth monitoring in the home telehealth group (2.4 ± 3.5) in comparison to the previous year without monitoring (4.1 ± 4.6, p < 0.0001) and to the control group (3.8 ± 5.3, p < 0.001). A significantly lower admission rate (1.1 ± 1.6) and length of stay (5.7 ± 11.3 days) were observed during home telehealth monitoring within the home telehealth group compared to the prior year (1.6 ± 1.7, p < 0.05 and 9.5 ± 14 days, p < 0.01 respectively) but not in comparison with the control group (1.4 ± 2.0, p < 0.07). The home telehealth group also had a significantly lower length of stay when compared to the control group (5.7 ± 11.3 vs 9.0 ± 14.9, p < 0.01). The number of urgent care and emergency room visits, or primary care visits, was not significantly different during home telehealth monitoring as compared to the prior year. Conclusions: Personalised and patient-centred home telehealth monitoring in heart failure patients was successful in reducing outcomes without an increase in outpatient and urgent care visits.